Gheda business family: a draft of the family constitution - Gheda, Carlo (2021)
The following work project aims to provide solid foundations for central keys tone of the business family’s long-term wellbeing: the Family Constitution. The Gheda family, its family business, and current main challenges will be presented at first. The importance of governance in family business systems and best practices for implementing a solid family constitution will be set through the literature review. Based on those sources, a methodology for collecting and analyzing data will be pursued to build the draft of the first version of the Gheda family constitution.